Analisis Faktor Yang Berhubungan Dengan Implementasi Sistem Informasi Manajemen Rumah Sakit (Simrs) Di Rumah Sakit Nurul Hasanah Kutacane Tahun 2022 - Amelia, Inneke Mutiara; Tampubolon, Elmina; Ariescha, Putri Ayu Yessi (Jurnal Inovasi Kesehatan Masyarakat, 2023)
Hospitals must be able to adjust the management of data, information and must increase the efficiency and effectiveness of hospital administration by carrying out the implementation of SIMRS. According to the Indonesian Ministry of Health (2019), in Indonesia it shows that at the end of 2018 only 48% of hospitals had used SIMRS and increased by 4.05% to 52.05% in September 2018. The rest, hospitals already had SIMRS but were not functioning properly (5%), did not have SIMRS (16%) and the rest did not report using SIMRS. Nurul Hasanah Hospital was one of the private hospitals in the city of Kutacane, Southeast Aceh District that implements SIMRS. The tipe of this research were correlational descriptive quantitative study by analyzing factors related to SIMRS Implementation at Nurul Hasanah Hospital Kutacane by using the HOT-Fit Model (Human, Organization, Technology). The researcher chosen this model because has given an explanation and evaluation of the factors of HR, Technology and Organization.The sample of this study were 31 structural officers and staffs at Nurul Hasanah Hospital Kutacane. Based on the results of partial statistical tests by using Logistic Regression has got influence between HR and Technology for SIMRS Implementation at Nurul Hasanah Hospital Kutacane.